Non-Redox-Based Electrochemical Detection of Adrenaline: A Simple and Reliable Approach Using Glass Nanopipets - Ralph J. Page; Gene Koifman; Noel Manring; Jessica L. Smeltz; Pavithra Pathirathna (Applied Sciences)
The detection of adrenaline (Adr) is essential for monitoring physiological and clinical conditions, including stress response, cardiovascular health, and neurological disorders. We present a novel glass-nanopipet electrode sensor based on a non-redox ion-transfer approach using ion transfer across two immiscible electrolyte solutions (ITIES). Two ionophores, dibenzo-24-crown-8 ether (DB24C8) and dibenzo-18-crown-6 ether (DB18C6), were evaluated for their ability to facilitate Adr transfer across aqueous/dichloroethane interfaces. Among these, DB24C8 demonstrated superior stability, attributed to its larger ring size and stronger complexation with Adr. We systematically studied Adr transfer in various media, including KCl, DI water, Millipore DI water, and Tris buffer, and constructed calibration curves based on peak potential shifts that follow a power-law relationship with Adr concentration. The sensor achieved a detection limit of 5 pM in Tris buffer using DB24C8 and 50 pM with DB18C6, both significantly lower than the physiological concentration of Adr. Furthermore, the effects of pH and ionic strength on the peak shifts were analyzed, revealing that pH changes had a more substantial impact compared to ionic strength variations. Importantly, while DB24C8 and DB18C6 are known to facilitate the transfer of other cations, such as potassium and calcium, our findings confirm that these cation transfers do not interfere with Adr detection. This innovative ITIES-based sensing platform offers ease of fabrication, robustness, and excellent potential for real-time, in vivo applications. It represents a significant advancement in electrochemical detection technologies, paving the way for practical applications in clinical and physiological settings.